Análisis de gestos deportivos de saque con salto en voleibol usando videometría - Guzman-Vargas, Karen-Daniela; Suarez-Baron, Marco-Javier; Torres-Pérez, Yolanda; González-Sanabria, Juan-Sebastián (Revista Científica, 2021)
In the game of volleyball, the technique to execute the serve gesture is essential to be able to hit the ball properly and thus score points against the opposing team. However, this gesture is not always carried out in an efficient biomechanical way, which generates bad shots to the ball and a disadvantage in the game. Therefore, the biokinematics of the technical-sports gesture of some players (experts in jump serve) of the volleyball team of the Universidad Pedagógica y Tecnológica de Colombia (Boyacá - Colombia), was studied and evaluated, using the videometry technique, with the objective of determining (qualitatively and quantitatively) trajectories, speeds, accelerations, and joint angles of joints such as: wrist, elbow, shoulder, hip, knee and ankle of the athletes executing the jump serve gestures, with which they were designed and implemented corrective interventions of the athletes’ movement in the jump serve gesture to generate a more efficient and ergonomic stroke during the serve.